Strengthened linkage between November/December North Atlantic Oscillation and subsequent January european precipitation after the late 1980s - Liu, Yang; He, Shengping (Journal of Climate, 2020)
This work investigates the nonsynchronous relationship between the North Atlantic Oscillation (NAO) and winter European precipitation. The results indicate that the linkage between early-winter (November and December) NAO and the following January precipitation and atmospheric circulation over the North Atlantic and European sectors became statistically significant after the late 1980s. Before the late 1980s, January precipitation and atmospheric circulation are weakly correlated with early-winter NAO. After the late 1980s, by contrast, the positive phase of the early-winter NAO is generally followed by an anomalous meridional dipole pattern with barotropic structure over the North Atlantic, which provides conditions for more (less) precipitation south of Iceland (east of the Azores). Further analysis elucidates that this regime shift may be partly attributed to the change of early-winter NAO, which is concurrent with significant change in the intensity of the synoptic and low-frequency eddy interaction over the Atlantic–European sectors. Anomalous positive sea level pressure and geopotential height, along with zonal wind anomalies associated with a positive early-winter NAO over the North Atlantic, are more significant and extend more northeastward after the late 1980s, which may be induced by an intensified transient eddy feedback after the late 1980s, as well as the enhanced storm-track activity over the North Atlantic. Thus, early-winter NAO can induce significant ocean temperature anomalies in the North Atlantic after the late 1980s, which extend downward into the middle parts of the thermocline and persist until the following January to trigger NAO-like atmospheric circulation patterns. Analyses from the Community Earth System Model large ensemble simulations indicate the effects of internal climate variability on such a strengthened linkage. publishedVersion